PSXI-35 Effects of cultivation stage and supplementation level of sprouted barley on nutrient content and fermentation quality of fermented diet - lee, Hyuk jun (J Anim Sci, 2019)
This study was aimed to estimate the effect of cultivation stage and supplementation level of sprouted barley (SB) on nutrient content and fermentation quality of fermented total mixed ration (TMR). The SB were collected at day 6 (SB6) and day 8 (SB8) of cultivation stages and substituted at 5% (TMR5) and 10% (TMR10) of TMR on dry matter (DM) basis. These TMR were ensiled into 10 L mini silo (3 kg) for 14 days in triplicate. After silo open, sample (1 kg) was collected for laboratory analysis. Before ensiling, crude protein (CP) was lower (P = 0.012) in SB6 than in SB8. Additionally, DM in TMR10 was slightly lower (P = 0.015) than in TMR5 while CP and acid detergent fiber were higher (P < 0.05). After fermentation, crude ash (P = 0.002), in vitro DM digestibility (IVDMD) (P = 0.001; 73.5 vs. 72.0%) and in vitro neutral detergent fiber (IVNDFD) (P = 0.001; 50.6 vs. 47.7%) were higher in SB6 than in SB8. Additionally, DM (P = 0.002; 64.0 vs. 64.5) in TMR10 was lower than in TMR5, while CP (P = 0.005; 19.7 vs. 18.9%), IVDMD (P = 0.001; 74.5 vs. 71.0%), and IVNDFD (P = 0.001; 52.0 vs. 46.3%) were higher. Fermentation indices and microbial counts were not affected by cultivation stage of SB, except on propionate that higher (P = 0.014) in SB8 than SB6. Silage pH (P = 0.001) was lower in TMR10 than in TMR5, which followed by higher lactate (P = 0.003; 3.27 vs. 2.85%), acetate (P = 0.004; 0.52 vs. 0.42%), propionate (P < 0.001), and LAB count (P = 0.020; 7.49 vs. 7.19%). The interaction effects between cultivation stage and supplementation level only found on propionate production (P = 0.001). Yeast and mold were not affected by cultivation stage and supplementation level of SB. This study concluded SB6 was recommended to improve fermentation quality of fermented diet, and its application on TMR10 could increase not only rumen digestibility but also fermentation indices. [Image: see text] [Image: see text] [Image: see text]